Study of the Effects of Gap Suction on Turbulent Separated Flows at Supersonic Speeds - Kania, W. (Engineering Transactions, 1975)
An experimental investigation was made to determine the effects of suction on supersonic turbulent boundary-layer seperation induced by a spoiler an a flat plate. The test model was the flat plate and the spoilers with and without a gap. It was shown that the length of separation region for spoiler with a gap expressed in normalized form by means of the spoiler height depend only upon ratio of gap and spoiler height. It was found that the seperation pressure is independent of suction. This study has indicated that the separation process induced by the spoiler with gap is free interaction type. The normalized pressure distribution in the fore region of the spoilers without and with a gap were found. The ratio of gap and spoiler heights was correlated with the normal force induced by the spoiler with a gap.